Turner : his life and works in 500 images - Robinson, Michael (London : Lorenz Books, 2010)
An exploration of the life and works of the painter Turner. It covers the entire period of his lifetime from the early years up until his death in 1851. It features an illustrated description and investigation of his life, his travels, his artistic influences and aspects of his personal life.
Includes index.
Keywords: Turner, J. M. W. -- 1775-1851.; Turner, J. M. W. -- 1775-1851 -- Criticism and interpretation